The effect of “Harry Potter and Philosopher’s Stone” movie in students’ British accent pronunciation - Mellyana, Intan; Ikhsanudin, Ikhsanudin; Wardah, Wardah (English Learning Innovation, 2024)
This study aimed to examine the impact of utilizing the Harry Potter movie, "Harry Potter and the Philosopher's Stone", as an educational instrument to facilitate the enhancement of year-9 SMP Negeri 06 Pontianak students' proficiency in British accent pronunciation. The research employed a pre-experimental research design, with a one-group pre-test and post-test approach, utilizing a sample of 30 IX C students selected through cluster random sampling methodology. The data were collected through pre-test and post-test assessments, which demonstrated that the result of the students' pre-test was lower than the post-test (85>16.67). Furthermore, the results indicated that the t-test exceeded the t-table value (28.47>1.699), thereby demonstrating a statistically significant effect. The results of the research analysis revealed that the null hypothesis was rejected while the alternative hypothesis was accepted. In addition, the effect size score (3.34) denoted a strong effect of the movie "Harry Potter and the Philosopher's Stone", which could be concluded that the Harry Potter movie had a very significant impact on students' ability to pronounce English words properly, particularly in British accent. The findings suggest the potential of the aforementioned movie as a medium for teaching British accent pronunciation to students, which despite on its initial purpose that the Harry Potter movie is recommended media to be used for teaching ninth-grade students.